83.3k views
23 votes
Solve for K 2(k - 5) + 3k = k + 6

1 Answer

7 votes

Answer:

k = 4

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtract Property of Equality

Algebra I

  • Terms/Coefficients

Explanation:

Step 1: Define

2(k - 5) + 3k = k + 6

Step 2: Solve for k

  1. Distribute 2: 2k - 10 + 3k = k + 6
  2. Combine like terms: 5k - 10 = k + 6
  3. Subtract k on both sides: 4k - 10 = 6
  4. Add 10 on both sides: 4k = 16
  5. Divide 4 on both sides: k = 4

Step 3: Check

Plug in k into the original equation to verify it's a solution.

  1. Substitute in k: 2(4 - 5) + 3(4) = 4 + 6
  2. (Parenthesis) Subtract: 2(-1) + 3(4) = 4 + 6
  3. Multiply: -2 + 12 = 4 + 6
  4. Add: 10 = 10

Here we see that 10 does indeed equal 10.

∴ k = 4 is the solution to the equation.

User Hexception
by
6.0k points